Sosialisasi K3 Tentang Implementasi Emergency Respon Plan Kantor Kelurahan Tembok Dukuh Kota Surabaya - Nikhen Hanifah Alvianshah; Moch. Sahri (Jurnal Pengabdian Pada Masyarakat, 2022)
OCCUPATIONAL SAFETY AND HEALTH SOCIALIZATION ABOUT IMPLEMENTATION OF EMERGENCY RESPONSE PLAN DISTRICT OFFICE TEMBOK DUKUH, SURABAYA CITY. Understanding Emergncy Response Plan and its facilities at tembok dukuh Sub District Office to improve security and alertness in dealing with disasters. Identification of K3 implementation problems, socialization of K3 and application of emergency Response plan, licensing as well as the application of emergency Response plan facilities in the form of evacuation routes are supported with open arms , so that the Tembok Dukuh village office arises a sense of alertness to natural disasters Community Service is carried out with the target of all Tembok Dukuh village office workers both civil servants (PNS) to outsourced labor. . Tembok dukuh village office basically still found many discrepancies in aspects of Occupational Safety and health (K3). Many work activities carried out in the office which certainly has a risk of danger, so K3 is needed. The village office is a workplace with most of the important administrative file archives and there is still a lot of potential for a fire such as electrical cables that are scattered. The office workers of Tembok Dukuh village do not fully have a disaster preparedness attitude and there is no supporting Emergency Response Plan facility. Seeing the real conditions in the village office, then with it carried out socialization of community service on K3, especially Emergency workers understand the education delivered premises evidenced by the response or feedback in the form of questions and sharing related to K3 offices, especially on the topic of Emergency Response Plan of workers. Socialization of Emergency Response Plan Basically must be owned and disipakan by all aspects of the work. In line with law No. 1 of 1970 article 3 which states that” providing an opportunity or way to save themselves during a fire or other dangerous events", the entire workplace needs an evacuation map which is interpreted as a description of the rescue path when an emergency occurs so that it is easier to do. In this socialization, participants were not only given a theoretical understanding related to the implementation of the K3 Emergency Response Plan, but participants were also introduced to related Emergency Response Plan facilities, one of which was in the form of evacuation routes.